(untitled) (Bangladesh Journal of Physics, 2023)
This work reports the effect of substrate temperature (TS) on the structure, surface morphology, optical, and electrical properties of iron (III) oxide (Fe2O3) thin films. Fe2O3 thin films were deposited from the aqueous solution of ferric chloride hexahydrate at various TS between 573 and 773 K using the spray pyrolysis technique. In field emission scanning electron and atomic force microscopic analysis, the surface of Fe2O3 films comprised nanoparticle clusters. In X-ray diffraction analysis, Fe2O3 thin films showed a rhombohedral-hexagonal structure with the predominant orientation along (104) crystallographic plane. Crystallite size reduced from 28 to 13 nm with the increase of TS between 573 and 773 K. In UV-vis- NIR spectroscopy, the highest transmittance was found to be 76% for the film deposited at the TS of 673 K. Band gap of the film was obtained between 2.05 - 2.09 eV. The electrical resistivity of the films ranged from 2.2 ´ 105 to 9.0 ´ 105 Ω-cm. The films contained n[1]type majority carriers with carrier concentration in the order of 1018 cm-3 . Fe2O3 thin films with wide band gap, high transparency, and n-type conductivity indicate that the films are suitable for Fe2O3 in optoelectronic applications. Bangladesh Journal of Physics, Vol. 30, Issue 1, pp. 13–22, June 2023